2023
DOI: 10.1093/jamia/ocad072
|View full text |Cite
|
Sign up to set email alerts
|

Using AI-generated suggestions from ChatGPT to optimize clinical decision support

Abstract: Objective To determine if ChatGPT can generate useful suggestions for improving clinical decision support (CDS) logic and to assess noninferiority compared to human-generated suggestions. Methods We supplied summaries of CDS logic to ChatGPT, an artificial intelligence (AI) tool for question answering that uses a large language model, and asked it to generate suggestions. We asked human clinician reviewers to review the AI-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(84 citation statements)
references
References 30 publications
3
79
0
2
Order By: Relevance
“…In a study, [24] a total of 36 AI-generated suggestions and 29 human-generated suggestions for 7 alerts were analyzed by 5 clinicians. Among the top 20 suggestions based on the survey scores, 9 were generated by ChatGPT.…”
Section: What This Knowledge Adds To What We Already Knewmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study, [24] a total of 36 AI-generated suggestions and 29 human-generated suggestions for 7 alerts were analyzed by 5 clinicians. Among the top 20 suggestions based on the survey scores, 9 were generated by ChatGPT.…”
Section: What This Knowledge Adds To What We Already Knewmentioning
confidence: 99%
“…[21] This study seeks to determine ChatGPT grade C for questions in the field of pediatrics, similar results to previous studies. [12][13][14]20,21,24] The potential for ChatGPT and future virtual assistants become important tools for patients and healthcare providers based on assessments ranging from basic fact-based questions to complex clinical questions in a study. [55] Although ChatGPT was able to provide interpretable responses that reduced the likelihood of causing alarm compared to Google's feature snippet, there is an urgent need for regulators and healthcare professionals to be involved in developing standards for minimum quality and to educate patients about the limitations of emerging AI assistants.…”
Section: What This Knowledge Adds To What We Already Knewmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, several studies have evaluated the value of ChatGPT for clinical decision support optimization. Their results showed that ChatGPT could be an important complementary part of optimizing clinical decision support and may even be able to assist experts in formulating their own suggestions [ 13 , 14 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…reasoning processes 4,5 . Beyond answering general questions, GAI has demonstrated effectiveness in specialized medical contexts 6 , including U.S. Medical Licensing Examination queries 7 , clinical decisionmaking consultations 8,9 , and medical research assessments 10,11 . Notably, ChatGPT is already being leveraged by biotechnology companies to suggest novel pathways for drug targets 12 .…”
mentioning
confidence: 99%